GENDER INCLUSION AND JUSTICE IN EDUCATION: A CRITICAL REVIEW BASED ON RESEARCH RESULTS - Apriliana, Teguh Firmansyah; Khoiroh, Nisaul; Utami, Cintara Prili Widya; Zania, Firda; Maspupah; Nuraeni, Dede Eni; Sudrajat, Mahdi; Priyonggo; Damayanti, Fitri (PT. Antis International Publisher, 2026)
Objective: This study aims to provide a comprehensive analysis of the implementation of gender inclusion and justice in education by examining policy frameworks and empirical research within Indonesian and global contexts. Method: Using a Systematic Literature Review (SLR) approach, the study integrates findings from 23 national and international indexed journal articles published between 2017–2025, complemented by relevant educational policies, to identify trends, barriers, and opportunities for gender-responsive educational practices. Results: The analysis reveals a substantial gap between established policies and their implementation, characterized by persistent gender stereotypes in curricula—especially in STEM fields—limited teacher competence in applying gender-responsive pedagogy, disparities in educational access between rural and urban regions, and inadequate representation of women in academic leadership. The findings emphasize the need for comprehensive pedagogical transformation supported by multi-stakeholder collaboration and strengthened GESI integration. Novelty: This study offers an intersectional synthesis of policy and empirical evidence, highlighting systemic inconsistencies and proposing an integrative framework for advancing gender-inclusive education practices across diverse learning environments.